2017
DOI: 10.1177/0963947017718997
|View full text |Cite
|
Sign up to set email alerts
|

Exploring new territories in pedagogical stylistics: An investigation of high-school EFL students’ assessments

Abstract: The growing number of recent publications on pedagogical stylistics indicates that this area is still of much interest to those who invest in the integration of language and literature. However, evidencebased assessments of pedagogical stylistics are still few and depend mostly on teachers' intuitions. The present study contributes towards filling this gap by examining 28 reflective accounts produced by highschool English as a foreign language (EFL) teenagers who participated in a literary awareness workshop o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Mentioned only eight times in six reflective accounts, some resented the fact that they were already familiar with iconicity. This criticism appears in Viana and Zyngier (2017) and Zyngier and Viana (2016) and must be interpreted alongside the students' proficiency levels as their command of English varied dramatically. This reveals the difficulty of teaching a mixed-ability class, a context which 'deserve[s] far greater professional attention in ELT' (Hedge 2000, 25).…”
Section: 'Materials' Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mentioned only eight times in six reflective accounts, some resented the fact that they were already familiar with iconicity. This criticism appears in Viana and Zyngier (2017) and Zyngier and Viana (2016) and must be interpreted alongside the students' proficiency levels as their command of English varied dramatically. This reveals the difficulty of teaching a mixed-ability class, a context which 'deserve[s] far greater professional attention in ELT' (Hedge 2000, 25).…”
Section: 'Materials' Findingsmentioning
confidence: 99%
“…reflective [Type here] accounts) and references per subcategory, value and category. Moving away from pedagogical stylistics(Viana and Zyngier 2017), this study examines the data with a view to providing a fine-grained analysis of perceived learning/teaching gains and losses.Table 2. Number of sources and references.…”
mentioning
confidence: 99%
“…Our previous studies indicated that the participants viewed the experience as pedagogically valid (cf. Viana and Zyngier 2017;Zyngier and Viana 2016). Here, we provided evidence that they also learned how to work with iconicity and found room to express themselves.…”
Section: ) Conclusionmentioning
confidence: 58%
“…Pedagogical stylistics has been the focus of a number of scholars (e.g. Burke, 2010; Carter, 1989; Clark and Zyngier, 2003; Giovanelli, 2010, 2016b, 2017; Short 1996; Viana and Zyngier, 2017; Widdowson, 1975; Zyngier, 2006; Zyngier and Fialho, 2010, 2015; Zyngier and Viana, 2016, amongst others) and the special-interest group of the Poetics and Linguistics Association (PEDSIG). Whilst many studies have discussed the aims and processes of pedagogical stylistics in a university context (e.g.…”
Section: Pedagogical Stylistics and The Re-contextualisation Processmentioning
confidence: 99%